Novel Food Grade Enzymes: Applications in Food Processing and Preservation Industries - Dutt Tripathi A.; Khosravi-Darani K.; Srivastava S.K. (My University, 2025)
This book covers all the aspects of food-grade enzymes, including their classification, kinetics, microbial production, biosynthetic pathways, commodity-wise industrial applications, and downstream processing strategies. The broad focus of this book is on the application of various classes of enzymes in dairy, fruits and vegetables, cereals and oilseeds, meat and poultry, and brewing and food packaging industries. Certain recent areas such as nanotechnological perspective in enzyme immobilization, infusion strategies as well as its efficient usage in food packaging and preservation are some of the salient highlights of this book. This book also discusses the aspects related to application of enzymes in functional food development and shelf life extension of various commodities food products. This book is beneficial for researchers, students, entrepreneurs, and industry experts in broad disciplines such as food processing, food biotechnology, food microbiology, biochemistry, agriculture, biotechnology, biochemical engineering, and bioprocess technology. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.